Inductively heatable catalytic materials for the dehydrogenation of the liquid organic hydrogen carrier (LOHC) perhydro dibenzyltoluene† - Schörner, Markus; Solymosi, Thomas Andrew; Raczka, Theodor; Nathrath, Phillip; Johner, Nicolas Patrick; Zimmermann, Thomas; Mandel, Karl; Wasserscheid, Peter; Wintzheimer, Susanne; Schühle, Patrick (Catalysis: Science and Technology, 2024)
Liquid organic hydrogen carriers (LOHC) represent a promising technology for future hydrogen storage and transport applications. For operations that require a certain hydrogen release dynamic (e.g. with fast load changes) the endothermal dehydrogenation of hydrogen-loaded LOHC compounds can greatly benefit from heating technologies that allow a fast hydrogen release with minimal energy losses. This contribution demonstrates that direct induction heating of the catalyst material represents a very interesting technology in this context as the catalyst material is heated specifically, and thus preheating times and heat losses to the environment can be avoided. In detail, this work highlights the dehydrogenation of perhydro dibenzyltoluene (H18-DBT) using inductively heatable Pt-based catalyst materials prepared in three different ways: a) Pt–alumina on steel beads, b) Pt–alumina on a flat FeCrAl-plate, and c) α-alumina core with a γ-alumina shell that contains spray-dried iron oxide (IO) nanoparticle agglomerates and is impregnated with P
Keywords: Hydrogen storage; Inductive heating; LOHC; Platinum; Perhydro benzyltoluene